Enhancing the Scattering Induced by Gold Periodic Arrays Over Optical Waveguides Through Indium Tin Oxide Buffer Layers - Rita Asquini; Alessio Buzzin; Nicolas Hanine; Alessia Mannetta; Badrul Alam; Vincenzo Ferrara (IEEE Photonics Journal, 2024)
This article presents the optical analysis on how the light coupling performance between optical channel waveguides and gold periodic nanoarrays in the visible spectrum can be improved using an indium tin oxide (ITO) thin film as buffer layer. Coupling efficiency, out-of-plane scattering and far-field projected beam focus and diffraction angle are evaluated using Finite-Difference Time-Domain (FDTD) method and scattering theory for different nanogratings and nanocylinders array patterns. The implementation of ITO enables up to a 12 fold increase in coupling efficiency, a 6.4 fold enhancement of light scattered out of the array plane and consequent improvements in the diffracted beam radiation intensity peaks, without compromising the beam's focus or altering its deflection angle. This configuration provides a cheap and simple solution to increase the device performance without changing the array features, for integrated biosensing and scattering-related applications.